Les entreprises marocaines et le développement durable: défis et enjeux. Illustration par le cas de l’OCP (site de Youssoufia) - Zammar, Rachid; Abdelbaki, Noureddine (European Scientific Journal, ESJ, 2016)
This article analyzes the challenges that the Moroccan companies namely Morocco’s Office Cherifien of Phosphate (OCP) in the Youssoufia site have to address in order to move towards sustainable development. It examines the necessary strategies for the implementation of such an approach and highlights the issues necessary for such a vision. It aims to answer the following question: what is the impact of the projects introduced by the OCP on the development of the city of Youssoufia? The research is based on a qualitative study conducted with some group leaders and directors of public institutions in the city of Youssoufia through semi-structured interviews. The main results of the evaluation are as follows: -at the environmental level: though the group has carried out several projects they do not help improve air quality nor reduce urban sprawl; - at the social level: the group has conducted several civic actions that are limited in time and do not help those who really need help. However, funding for associations’ activities remains reserved and unsustainable, many unfulfilled commitments as the schools that have no adequate water facilities.